KAJIAN HUKUM TERHADAP TINDAK PIDANA PENIPUAN DENGAN DASAR HUTANG PIUTANG - Syawal Amry Siregar; Kristofel Ablio Manalu (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2021)
The form of responsibility for the perpetrator in a criminal act of fraud on the basis of accounts payable is to follow the existing procedures, from the investigation process to the detention process. This research method is normative juridical. The formulation of the problem under study is what is the form of fraud on the basis of accounts payable; What is the form of legal protection for victims of criminal cases of fraud on the basis of accounts payable and what is the form of accountability of the perpetrators for criminal acts of fraud on the basis of accounts payable. The result is a form of fraud on the basis of accounts payable, including the criminal act of fraud in the Criminal Code regulated in Book II concerning Crimes against Assets, which is in the form of attacks on people's legal interests for their property and fraud on the basis of accounts payable related to money lending and borrowing problems (accounts payable).